Managing Russian Science-Intensive Enterprises in the Emerging New Technological Paradigm - Veselovsky, Mikhail Yakovlevich; Suglobov, Alexander Evgenievich; Abrashkin, Mikhail Sergeyevich; Khoroshavina, Natalya Sergeevna; Stepanov, Alexander Annayarovich (International Review of Management and Marketing, 2016)
The main purpose of the work was to examine the characteristics and identify the most innovative ways to manage Russian science-intensive enterprises in the emerging new technological paradigm. Fundamental position, works of scientists authoritative in this field, and author's developments served as theoretical and methodological basis of the research. The main methods of the research were the methods of empirical knowledge. As a result of the work, it is proposed to redefine the economic development strategy of the Russian Federation from the established resource-based scenarios to the most progressive ones that imply improvement of scientific and technological development of a number of industries to competitive international levels, to new technological paradigms. The necessity is founded to strengthen the effectiveness of the science-intensive enterprises, which act as a "core" of the production of innovative products, point of formation of a new post-industrial technological paradigm and the foundation of long-term economic growth in Russia. The peculiarities of the activities of science-intensive enterprises in the context of improving the approach to planning and forecasting are revealed. The necessity of harmonization of managing the science-intensive enterprises and the strategies of the state development of scientific and industrial base are methodologically founded. A set of instruments of state support for science-intensive enterprises that allow to bring Russia to the path of sustainable economic growth based on innovation is provided. Keywords: Science-Intensive Enterprises, Science-Intensive Industries, Innovations, Technological Paradigms. JEL Classifications: O31, O32, O33, O43.